Hearing Improvement Following Middle Cranial Fossa Floor Defect Repair Utilizing a Modified Middle Fossa Approach and Reconstructive Techniques. Issue 8 (September 2019) - Alwan, Mostafa; Ibbett, Imogen; Pullar, Michael; Lai, Leon T.; Gordon, Michael
Abstract : Background: Few studies report hearing preservation following middle cranial fossa (MCF) floor defect repair. Objective: To investigate audiological outcomes following MCF floor defect repair using a modified MCF suprapetrous approach. Study Design: Retrospective cohort. Setting: Tertiary referral center. Patients: Eleven patients, with MCF floor defects. Interventions: MCF floor defect surgical repairs with either fascia or fascia and bone graft. Main Outcome Measured: Hearing outcomes. Results: Eleven patients (two men) aged 34 to 82 years (median, 62 yrs) were identified. All patients were operated on by the same two senior surgeons (M.P. and M.G.). One patient with conductive hearing loss (based on tuning fork test) was excluded from the analysis due to missing preoperative audiogram data. All patients had middle fossa plate defects leading to cerebrospinal fluid (CSF) otorrhoea, rhinorrhoea, or meningitis. Nine patients had retrieval of herniated contents from the defect. Five patients had repair with temporalis fascia and split calvarial bone graft, and six patients had repair with fascia only. Follow up audiogram was performed at a mean 7.5 months (range, 0.5–24 mo). There was no recurrent CSF leak during the follow up period. The 10 patients (90.9%, 95% confidence interval [CI] 60.1–100.6) who had complete audiologic data sets demonstrated a mean improvement of 18.86 dB (range, –7.5 to 33.75 dB) in hearing postoperatively. One of these patients acquired a 7.5 dB reduction in postoperative hearing due to post-procedural middle ear effusion which subsequently resolved. Hearing improvement following fascial graft alone versus fascial graft with bone was 12.5 and 26.5 dB, respectively ( p < 0.01). Conclusion: Middle fossa craniotomy with or without retrieval of herniated contents and floor reconstruction with fascia and bone is associated with improved hearing. Clinical efficacy of this technique, however, can be only fully established when a statistically meaningful number of cases have been performed.